ONLINE MARKETING STRATEGY TO INCREASE SALES TURNOVER IN THE SOUTH LAMPUNG TAPIS CLOTH HOME INDUSTRY USING SWOT ANALYSIS - Muslihun, Muslihun (STMIK Pringsewu, 2024)
Study This aim for analyze online marketing strategies in increase turnover sales in home industry Tapis cloth in South Lampung. Tapis cloth is one of them product craft Typical of Lampung which has wide market potential, both domestically and internationally international. However, in face increasing competition strict, home industry Filter cloth is necessary adopting effective marketing strategies, for one through online marketing. Method used in study This is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats), which involves identification Internal and external factors that influence home industry Tapis cloth. Analysis This help in formulate the right strategy for increase Power competition and turnover sale. Research result show that home industry strengths Tapis fabric lies in quality high quality and unique products design traditional. However, weaknesses include limitations in understanding digital technology and limitations source Power man. Main opportunities is increasing trend online shopping and requests to product local. Temporary that is, the threats faced including competition from product kind and change fast market trends. Based on SWOT analysis, is recommended several online marketing strategies that can be applied, like social media optimization, e-commerce usage, and improvements digital skills of actor industry. With implementation of this strategy, it is hoped that the home industry South Lampung Tapis cloth available increase turnover sales and expand market reach significant.